The economic and social effects of the EU Free Trade Agreement (DCFTA) with Tunisia - Jan Grumiller; Werner G. Raza; Cornelia Staritz; Bernhard Tröster; Rudi von Arnim; Hannes Grohs (Austrian Foundation for Development Research (ÖFSE), 2018)
The EU has recently concluded or is currently in the process of negotiating a number of bilateral free trade agreements with both industrialized countries, e.g. Japan, and developing as well as developing and emerging economies. Negotiations with the latter group include Tunisia, where negotiations on the Deep and Comprehensive Free Trade Agreement (DCFTA) were formally launched in October 2015. Until July 2018, two negotiation rounds have taken place, the conclusion of the agreement is expected for 2019. Based on the EU trade strategy "Trade for All. Towards a more responsible trade and investment policy", published in October 2015, these so-called new generation bilateral trade agreements are deliberately designed as 'deep and comprehensive". In other words, while also targeting remaining traditional trade barriers, such as tariffs and quotas, above all they aim at tackling non-tariff measures that are deemed relevant for trade. As is also stressed by the EC, trade liberalization in the extended definition of the new EU trade agenda must promote sustainable development both in the EU and the partner countries, i.e. economic growth that is socially inclusive and respects ecological boundaries. In other words, adherence to the principle of policy coherence for sustainable development (PCSD), as recently defined by the UN Agenda 2030 for Sustainable Development and subsequently adopted by the new European Consensus on Development, is required. New generation FTAs are therefore primarily to be assessed against this yardstick, which is the approach adopted in this study with respect to the EU FTA with Tunisia (DCFTA). The report assesses the DCFTA between the EU and Tunisia, starting with an economic overview and an analysis of the trade patterns between the EU and Tunisia (Section 2). In the following section, the key contents of the FTAs are assessed (Section 3). This includes a detailed analysis of the market access offer and other key issues, as well as a discussion of the trade and sustainable development aspects of the respective agreement, and finally of EU development cooperation in the partner country. Section 4 analyzes the economic implications of the FTAs on Tunisia. The section starts with an assessment of the potential economic impacts of the agreement, based on simulations with the ÖFSE Global Trade Model. Based on interviews with stakeholders and field research in the partner country, negotiating concerns and implementation challenges associated with the agreement are detailed in the subsequent sections. Further, different sector case studies are analyzed in order to investigate the potential of the DCFTA on the export side, highlighting the opportunities and challenges for export promotion policies in the context of global value chains and related lead firm strategies as well as local competitiveness conditions. The sectoral case studies include the textile and apparel sector as well as the olive oil sector in Tunisia. Section 5 provides a summary of the main findings with respect to economic impacts, the sectoral case studies and the sustainability concerns. Upon that basis, key policy recommendations are proposed in the areas of adjustment assistance and productive development promotion.
Additional information: Final report, 12 July 2018
Keywords: 330